Circulating Placental Vesicles Carry HLA-DR in Pre-Eclampsia: A New Potential Marker of the Syndrome - Tersigni, Chiara; Lucchetti, Donatella; Franco, Rita; Colella, Filomena; Neri, Caterina; Crispino, Laura; Sgambato, Alessandro; Lanzone, Antonio; Scambia, Giovanni; Vatish, Manu; Di Simone, Nicoletta (Frontiers in Immunology, 2021)
Background: Pre-eclampsia (PE) is a common disorder of pregnancy that usually presents with hypertension and proteinuria. The clinical presentation arises from soluble factors released into the maternal circulation from the placenta owing to the stress of syncytiotrophoblast, consequence of defective placentation occurring in the first half of pregnancy. Reduced tolerance of the semiallogeneic fetus by the maternal immune system has been proposed as first trigger leading to poor placentation. We previously observed aberrant expression of human leukocyte antigen (HLA)-DR molecules in the syncytiotrophoblast of a subset of women with PE. Aim of this study was to investigate abnormal expression of circulating HLA-DR in syncytiotrophoblast-derived extracellular vesicles (STEVs) in women with PE compared to normal pregnant women. Methods: peripheral venous blood was collected from 22 women with PE and 22 normal pregnant women. Circulating STEVs were collected by ultra-centrifugation (120000 g) and analyzed for the expression of HLA-DR and placental alkaline phosphatase (PLAP), a specific marker of the placenta, by Western blot analysis and flow cytometry. Results: circulating STEVs positive for HLA-DR were observed in 64% of PE women while no HLA-DR positivity was detected in any of the controls (P<0.01). Conclusions: Aberrant expression of HLA-DR in circulating STEVs is specifically associated to PE. Further studies are required: a) to define the role of aberrant placental expression of HLA-DR molecules in the pathogenesis of PE; b) evaluate a possible application of detecting circulating HLA-DR positive STEVs in the diagnosis and prediction of PE in the first and second trimester of pregnancy.